Avoidance of Over Speed Through Intelligent Speed Breaking System - M S Satyanarayana; Aruna T M; Divya G N (Institute of Advanced Engineering and Science, 2018)
Accidents have become major issue in Developing countries like India now a day. As per the Surveys 60% of the accidents are happening due to over speed. Though the government has taken so many initiatives like Traffic Awareness & Driving Awareness Week etc.., but still the percentage of accidents are not getting reduced. In this paper a new technique has been introduced in order to reduce the percentage of accidents. The new technique is implemented using the concept of Intelligent Speed Braking System. The Intelligent Speed Braking systems can be implemented any where essential in order to avoid the accidents. The main objective of this system is to calculate the speed of the vehicle at three different locations based on the place where the vehicle speed has to be controlled and if the speed is greater than the designated speed in that road then it will automatically open up the speed breaker to control the speed of the vehicle. If the speed is less or equal to the designated speed in that road then the vehicle will be passed without any disturbance. This system though it won’t avoid 100% accidents at least it will reduce the percentage of accidents. This is system is not only to avoid accidents it will also intelligently controls the speed of the vehicles and creates awareness amongst the drivers.